PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN SINGAPORE DI KOTA MAKASSAR - faisal hardiansyah; Mahmud Nuhung; Ismail Rasulong (Universitas Muhammadiyah Makassar, 2019)
The type of research used in this study is quantitative. The population in this study were all consumers who visited the Singapore restaurant. Sampling using nonprobability sampling, with type of accidential sampling method. Data collection techniques using questionnaires with Likert scale that each has been tested and has fulfilled the validity and reliability requirements. Data analysis technique used in this research is multiple linear regression. The result of multiple linear regression analysis shows that the variables of location and price simultaneously have a positive relation to consumer purchase result. This can be proven from the value of Fcount(14,649 ≥ 5,698) with a significance value (sig) of 0.00 ≤ 0.05 (a = 5%). The result of multiple linear regression analysis showed that Based on the result of t test the location variable is negative with tcount of 0,319 ttable value 2,051 and significance value equal to 0,752 ≤ 0,05. This indicates that location variable has negative and insignificant effect to purchasing decision variable and based on result of t test of positive value variable with tcount value 5,406 ≤ ttable value 2,051 and significance value equal to 0,00 ≥ 0,05. This shows that the variable of product price have positive and significant effect to consumer purchase decision variable.